An Investigation of Errors Committed by the Students of English Language Teaching Department in Writing Narrative Text - Aniuranti, Asfi; Wulandari, Yasinta; Tsani, M.Happy Nur (ELLITE, 2020)
In the EFL context, an error analysis is a paramount study. This type of research might bring many advantages to the success of the teaching and learning process itself. This study investigates the types and causes of student errors in writing a narrative text. Furthermore, this research provides several suggestions for decreasing the occurrence of the errors. The research method employed was descriptive qualitative, and the researchers completed this study through several phases called data gathering, data analysis, and data presentation. The data analysis reveals several significant findings. First, there are six types of errors that emerged called the use of tenses, the use of articles, the use of relative pronouns, mistyping, confusing words, and agreement of singular/plural nouns. Second, the interlingual transfer is the most significant factor causing errors. Third, decreasing the errors might be done by paying more attention to global errors, the errors with high frequency, the most influential error type, and the most problematic topic. In this present study, the kind of error requiring more attention is English tenses, and one of the suggested solutions for teaching tenses well is using attractive teaching media such as English songs. Applying effective ways of teaching is an alternative to reduce student errors.